Produção de mudas de pimentão (Capsicum annuum L.) em diferentes ambientes e substratos - Monteiro Neto, João Luiz Lopes (2016)
Producing Pepper seedlings quality is essential to obtain vigorous and productive plants in the field. These can be obtained from the control and exploitation of environmental factors and the use of substrates available in each region. Thus the present study evaluated the influence of five environments (1 - agricultural greenhouse, 2 - red fotoconversora screen with 35% shade, 3 - Red fotoconversora screen with 50% shade, 4 - silver fotoconversora screen with 35% shade and 5 - fotoconversora silver screen with 50% shading) linked to five substrates substratos (1 – OrganoAmazon®; 2 - OrganoAmazon® + PuroHumus® v/v; 3 - OrganoAmazon® + PuroHumus® + soil + manure v / v; 4 - Organ Amazon® + Pure Humus® + soil + manure + CAC v / v and S5 - OrganoAmazon® + PuroHumus® CAC + v / v) in the production of Pepper seedlings. The experiment was conducted in the experimental area of Agricultural Sciences Center of the Federal University of Roraima - CCA / UFRR in Boa Vista-RR, in the months from July to September 2015. The design was completely randomized in a split-plot scheme, totaling 25 treatments from the combination of the five environments (plots) with five substrates (subplots), with five replications of each experimental unit five plants. Quantitative and qualitative variables of the seedlings were analyzed. Data were submitted to analysis of variance, and when significant, applied the Scott-Knott test at 5% probability to compare the averages. The environments studied were divergent as the assessed microclimate characterization. The agricultural greenhouse is the best environment for the production of pepper seedlings, especially when associated with the substrate format by mixing compounds OrganoAmazon® + PuroHumus®. The substrate formed by OrganoAmazon® + PuroHumus® + soil + cattle manure (1: 1: 1: 1 v/v) was presented as an alternative to the production of pepper seedlings. The fotoconversoras screens do not promote conditions favorable to the production of quality pepper seedlings in Boa Vista, RR.